2012
DOI: 10.1155/2012/250352
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between a Top Order Predator and Exotic Mesopredators in the Australian Rangelands

Abstract: An increase in mesopredators caused by the removal of top-order predators can have significant implications for threatened wildlife. Recent evidence suggests that Australia’s top-order predator, the dingo, may suppress the introduced cat and red fox. We tested this relationship by reintroducing 7 foxes and 6 feral cats into a 37 km2fenced paddock in arid South Australia inhabited by a male and female dingo. GPS datalogger collars recorded locations of all experimental animals every 2 hours. Interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 55 publications
1
81
0
Order By: Relevance
“…Dingoes are successfully controlled using baits, while cats are more selective, less likely to eat carrion, and therefore less likely to consume baits (Claridge et al 2010). Current widespread control efforts are selective against dingoes and have led to mesopredator release of cats (Glen et al 2011;Moseby et al 2012). This was also evident in my study area (Chapter 2).…”
Section: Management Implications and Future Researchmentioning
confidence: 67%
See 4 more Smart Citations
“…Dingoes are successfully controlled using baits, while cats are more selective, less likely to eat carrion, and therefore less likely to consume baits (Claridge et al 2010). Current widespread control efforts are selective against dingoes and have led to mesopredator release of cats (Glen et al 2011;Moseby et al 2012). This was also evident in my study area (Chapter 2).…”
Section: Management Implications and Future Researchmentioning
confidence: 67%
“…In Australia, Cupples et al (2011) found extensive dietary overlap between dingoes and foxes (Pianka's index > 0.84), and found evidence of dingoes killing foxes. There is also experimental evidence of dingoes killing cats (and foxes) resulting from interference predation (Moseby et al 2012). And, cats have been documented killing quolls (Doherty et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations